Dataset for evaluating fitness index using Adaptive Neuro-Fuzzy Inference System - Chaitanya Kulkarni (Data in Brief, 2018)
With the current global downturn, the organizations need to develop new strategies and innovative approaches to ensure that every aspect of sustainability is achieved. For this purpose, the organizations need an indicator that measures the fitness if an organization. The purpose of this project is to analyze the ‘Fitness’ of an organization using the dataset related to leanness, agility and sustainability in ANFIS (Adaptive Neuro-Fuzzy Inference System) in order to determine whether the company is fit enough to sustain in global markets or not. The project does so by integrating both neural networks and fuzzy logic principles with lean, agility and sustainability principles. FIT manufacturing is the integration of Lean, Agile and sustainability manufacturing in one system as a whole which would help in attaining maximum output and sustain effectively in global markets. FIT Manufacturing adopts an integrated approach towards the use of Lean, Agility and Sustainability to achieve a level of fitness that is unique to each company. The database in the paper contains lean, agile and sustainable indices reviewed by experts. FIT does not prescribe that every aspect of Lean, Agile and Sustainability methodologies must be applied to every company, but a selective mix of components will provide the optimum conditions for a company to prosper.